Relacje z klientami w tworzeniu przewagi konkurencyjnej przedsiębiorstw - Daszkiewicz, Magdalena; Waniowski, Paweł (Customer Relations in Creating Competitive Advantage of Firms, 2008)
The aim of this article was to analyse the influence of customer relations on competitive advantage of firms. The starting point of these considerations is definition of key success factors in communication with clients. The authors describe the scope of activities used in communication with customers. The authors define benefits from shaping the positive corporate image in eyes of customers, paying special attention to the role of corporate image in consumer decisions. In summary of the considerations the authors describe basic problems connected with integrated systems of Customer Relationship Management.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 33, s. 94-106